Detection of pregnancy risk: A Literature Review - Indriani, Ririn; Wahyuni, Sri; Susiloretni, Kun A (STRADA : Jurnal Ilmiah Kesehatan, 2020)
In the millennial era unhealthy eating patterns and lifestyles associated with excess weight gain (obesity), diabetes mellitus, cholesterol and pregnancy complications, concomitant diseases such as heart disease, cholesterol, mothers exposed to alcohol, cigarettes or narcotics must be know. This study aimed to know the effectiveness of media books for pregnancy detection. The keywords used were detection of pregnancy risk, symptoms and signs of pregnancy. This literature review used articles from Google Scholar, Science Direct, Pubmed, DOAJ published from 2010 to 2020. The inclusion criteria are full text articles, using English language, survey research, workshop, and pilot study to health promotion. The exclusion criteria are articles was non English language, incomplete articles, case study. Containing symptoms and danger signs is effective for risk detection in early pregnancy